Sedum ince (Crassulaceae), a new species from Southern Anatolia - 'T Hart, H.; Alpinar, K. (Edinburgh Journal of Botany, 1999)
The newly described white-flowered annual Sedum ince closely resembles S. eriocarpum and the annual forms of S. hispemicum (S. longibracteatum), but differs from the former by its alternate instead of verticillate leaves, and from the latter by the 5-merous instead of 6 9-merous flowers and the ripe follicles which are divergent instead of patent and lack the distinct lips along the ventral suture. Molecular phylogenelic analyses indicate that S. ince is but distantly related to S. eriocarpum as well as to S. hispemicum. It belongs to a cytological distinct lineage of Sedum subgenus Gormunia sporting a basic chromosome number of x = 7. Within this lineage, however, S. ince holds a unique position and consequently it is classified in the monotypic S. series Elegans.
Keywords: Chloroplast DNA; Crassukiceae; flora of Turkey; new species; Sedum